An Electrical Plasma Surgery Tool for Device Replacement-Retrospective Evaluation of Complications and Economic Evaluation of Costs and Resource Use - KYPTA, ALEXANDER; BLESSBERGER, HERMANN; SALEH, KARIM; HÖNIG, SIMON; KAMMLER, JÜRGEN; NEESER, KURT; STEINWENDER, CLEMENS (Pacing and clinical electrophysiology, 2015)
Background Device replacements bear many potential risks for patients. Electrocautery should be used cautiously because of heating of the cautery tip which may lead to insulation melting. The PEAK PlasmaBlade™ (Medtronic Inc., Minneapolis, MN, USA) uses a novel technology to cut tissue. The objective of this study was to evaluate if this instrument is less destructive and can decrease complications and shorten procedure times. Methods and Results Two groups were compared: in group 1, surgery was done with scissors and conventional electrocautery, whereas the PEAK PlasmaBlade™ was used in group 2. Procedure time and complication rates were retrospectively investigated. Group 1 comprised 509 patients, while group 2 consisted of 102 patients. Procedure time in group 2 was significantly shorter with 28.4 ± 8.9 minutes than in group 1 with 47.5 ± 24.5 minutes (P < 0.001). The hospital stay was also reduced (2.1 ± 2.2 days versus 3.1 ± 2.4 days, P < 0.001). One major complication occurred in only 2.4% (two patients) of group 2 and in 6.9% (35 patients) of group 1. There were no damaged leads in group 2 compared to 5.7% in group 1 (P = 0.008). Cost analyses showed that the use of The PEAK PlasmaBlade™ instead of conventional electrocautery resulted in cost savings of €120/patient. Conclusion Device replacement is associated with a notable complication risk. Our investigation showed that a new device for generator replacement resulted in significantly reduced procedure time and length of hospital stay while completely avoiding lead damage, which translated into considerable cost savings in a real world setting.